THE STRUCTURAL ROLE OF USER CLASS IN CHAT INTERACTIONS ON TWITCH - Cahill, Tiernan (AoIR Selected Papers of Internet Research, 2018)
Twitch.tv has become an important platform for video streaming, especially of games, with more than 100 million monthly users. The structure of content on the platform, which merges live video feeds with chat rooms for user feedback, problematizes existing theoretical frameworks for understanding the roles and hierarchies of different types of users. Combined with efforts to monetize user engagement for the benefit of both platform owners and user-generators of content, there is a need for greater understanding of the new interaction paradigm introduced by the platform. The present study introduces a framework for systematic, quantitative analysis of user interactions in the chat rooms associated with Twitch channels, as well as a preliminary data set. Social network analysis techniques are used to analyse the centrality and homophily of different classes of users, and the theoretical significance of these observations is briefly discussed.